MILK QUALITY OF DAIRY GOAT BY GIVING FEED SUPPLEMENT AS ANTIOXIDANT SOURCE - Mardalena, M.; Warly, L.; Nurdin, E.; Rusmana, W.S.N.; Farizal, F. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
Free radical levels can be higher than the level of endogenous antioxidants in the body so thatuncomfortable conditions in the body of dairy goats could happen. To anticipate this uncomfortableconditions will be given feed supplement (FS) as source of antioxidants (AOX). FS contain mixturepineapple rind meal and antioxidant minerals (AOXM) each 25 ppm Zn and 10 ppm Cu. Thisexperiment was carried out to investigate the effect of feed supplements as antioxidant source on milkquality of dairy goats. Sixteen Etawah dairy goats in the second lactation were used in the experimentthat conducted using randomized block design with 4 treatments and 4 replicates. The treatments wereR0 (grass + concentrate), R1 (R0 + FS containing 0.04 % AOX), R2 (R0 + FS containing 0.06% AOX),R3 (R0 + FS containing 0.08 % AOX). The data collected were analyzed using Anova. The result ofphytochemicals analysis indicated that feed supplement contained flavonoid, polyphenols, sesqiuterpen,mopnoterpen, steroids, quinones and saponins. The results of study showed that there were difference(p<0.05) among treatments on blood and milk cholesterol and milk lactose, but there were no difference(P>0.05) on milk yield, milk fat, milk protein and milk antioxidant. The conclusion of this study was thefeed supplements containing 0.08 AOX produced the best response to milk quality of dairy goats.